Perancangan Arsitektur Sistem Aplikasi DOOR to DOOR Kantor UPPD SAMSAT Kota Salatiga Berbasis Android - Firda Rachman; Sri Yulianto Joko Prasetyo (Journal of Information System Research (JOSH), 2021)
The increase in the number of motor vehicles is difficult to anticipate, the roads used are not in accordance with capacity. To prevent congestion, the government imposes a progressive tax on motor vehicles that have moved owners but are still on behalf of the previous owner. Manunggal Administration System under One Roof (SAMSAT) conducts Door To Door activities to request direct confirmation to taxpayers whose vehicles are subject to progressive taxes. It is difficult for taxpayers to find out what makes data manipulation happen. Created Android-based Door to Door Application System using waterfall method to facilitate Door to Door activities and avoid manipulation of taxpayer data. By using waterfall method this application is made starting from the analysis of needs, design of system design, implementation, to the application of the program. Application system design is built using UML (Uniferd Modeling Language) system design and system design implementation using Android Studio and RestAPI.